2018
DOI: 10.1177/1558925018820722
|View full text |Cite
|
Sign up to set email alerts
|

Stretch properties of elastic knitted fabric with pillar stitch

Abstract: Knitted fabrics and products are subjected to a variety of stresses and loads/deformation during their usage. The loads are different by value, by direction, and by duration. The alternations of loading and unloading or resting processes affect the knitted structure and could bring about changes in the linear dimensions of the fabric or result in the deformation of the knitted items and ultimately the loss of product appearance or its functional properties. A wide range of textile materials resistant to multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Owing to their structural characteristics, knitted fabrics have excellent stretchability. 27 Spandex, contrastingly, is elastic because the so segment is deformed by an external force owing to its polymer structure composed of so and hard segments. 28,29 Therefore, the linear resistance increased as the silver layer on the surface was partially damaged, as the ber, and not the fabric structure, was stretched during elongation in the course direction.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to their structural characteristics, knitted fabrics have excellent stretchability. 27 Spandex, contrastingly, is elastic because the so segment is deformed by an external force owing to its polymer structure composed of so and hard segments. 28,29 Therefore, the linear resistance increased as the silver layer on the surface was partially damaged, as the ber, and not the fabric structure, was stretched during elongation in the course direction.…”
Section: Resultsmentioning
confidence: 99%
“…Materials made using knitting technology are known to have improved comfort properties, especially when elastane yarns are also used for plating. The previously published researches showed that the content of elastane in the material structure has a significant influence on the elastic properties (primary elastic recovery) of the materials [ 25 , 26 ]. The results of the measured breaking elongation of the investigated materials confirmed this evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas elastic warp knitted fabrics have stretch % up to 165%. 6 It was concluded that stretch in cotton covered elastane specimens back side was higher to specimens with spun polyester and cotton on back side. The core spun yarn having elastane adds the considerable stretching property in seersucker fabric as compared to others.…”
Section: Fabric Stretchmentioning
confidence: 98%
“…5 Olena Kyzymchuk and Liudmyla Melnyk suggest that linear density of inlay yarn and its tension are the main parameters to engineer the elastic properties of knitted fabric. 6 Surface evenness in knitted fabric can be created by use of a bi-component helical twisted yarn which is visible in greige fabric. 7 Different yarn and fabric parameters are engineered to optimize the comfort and other required properties of knitted and of woven fabrics by different researchers.…”
Section: Introductionmentioning
confidence: 99%